2021
DOI: 10.1038/s41467-021-24077-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive plasma glycomic and metabolic biomarkers of post-treatment control of HIV

Abstract: Non-invasive biomarkers that predict HIV remission after antiretroviral therapy (ART) interruption are urgently needed. Such biomarkers can improve the safety of analytic treatment interruption (ATI) and provide mechanistic insights into the host pathways involved in post-ART HIV control. Here we report plasma glycomic and metabolic signatures of time-to-viral-rebound and probability-of-viral-remission using samples from two independent cohorts. These samples include a large number of post-treatment controller… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 69 publications
(105 reference statements)
1
40
0
Order By: Relevance
“…Metabolomics analysis was performed as described previously ( 145 , 146 ). Briefly, polar metabolites were extracted with 80% methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolomics analysis was performed as described previously ( 145 , 146 ). Briefly, polar metabolites were extracted with 80% methanol.…”
Section: Methodsmentioning
confidence: 99%
“…In these investigations, people with HIV (PWH) interrupt antiretroviral treatment (ART) to test whether experimental interventions can keep HIV suppressed in the absence of therapy. Despite ongoing research [3][4][5], there is currently no biomarker available that can accurately predict when virus will return for a given participant. Frequent viral load testing during ATIs is necessary to detect viral rebound and determine when participants must restart ART [1].…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity of this measurement, its associations with TTVR or viral remission have not been evaluated frequently. However, one recent study found that lower levels of defective and hypermutated, but not intact, HIV DNA associated with delayed viral rebound [25]. In the same study, the lower levels of intact, defective, and hypermutated HIV DNA were associated with a higher likelihood of achieving a PTC phenotype after ATI [25].…”
Section: Viral Biomarkers Of Time-to-viral-rebound and Post-treatment...mentioning
confidence: 87%
“…As a consequence, these assays overestimate the size of replication-competent reservoirs. Despite this limitation, the pre-ATI levels of total HIV DNA have been associated with TTVR [12,24,25] as well as with post-treatment control [26,11,27,25,28,29]. However, such associations have not been consistent.…”
Section: Viral Biomarkers Of Time-to-viral-rebound and Post-treatment...mentioning
confidence: 95%
See 1 more Smart Citation